Parent–child attachment and adolescent problematic behavior: the mediating effect of legal emotions - Jianhua, He; Su, Xu; Shuhui, Xu (Frontiers in Psychology, 2025)
IntroductionIn criminology, the close relationship between legal emotions and adolescent deviant behavior is well-documented. In psychology, parental attachment is strongly associated with children’s problematic behavior; however, the role of legal emotions in this relationship remains underexamined.MethodsThis study investigates the role of legal emotions in the relationship between adolescent parent–child attachment and problematic behavior. Adolescents completed self-report questionnaires.ResultsResults revealed that both paternal and maternal attachment significantly negatively predicted adolescent problematic behavior, with paternal attachment explaining a larger proportion of the variance. Even after controlling for factors such as gender and grade level, parental attachment significantly negatively predicted adolescent problematic behavior. Legal emotions partially mediated the relationship between parental attachment and problematic behavior.ConclusionThese findings suggest that fostering positive parent–child relationships and enhancing adolescents’ positive legal emotions may be effective strategies for reducing problematic behaviors among youth.